Shifting the Ground of Canadian Literary Studies - Zacharias, Robert, 1977-; Kamboureli, Smaro (Book collections on Project MUSE., 2012)
Smaro Kamboureli's introduction demonstrates that these essays engage with the larger realm of human and social practices - throne speeches, book clubs, policies of accommodation of cultural and religious differences, Indigenous thought about justice and ethics - to show that literary and critical work is inextricably related to the Canadian polity in light of transnational and global forces."--Pub. desc.